Urgensi Perlindungan Hukum Perdagangan Elektronik Dalam Perspektif Persaingan Usaha di Indonesia - Muhammad Rizqy Fadillah (TIN: Terapan Informatika Nusantara, 2023)
This study aims to elaborate the form of legal protection for electronic commerce (e-commerce) as one of the important exponents in economic circulation in Indonesia. With juridical-normative research methods and literature study approaches, this research examines the legal protection of electronic commerce with an analytical instrument from a business competition perspective. The rapid development of e-commerce, which transformatively takes over the dominance of capital and market circulation, requires the government to adaptively prepare legal instruments that can provide extra protection, both for e-commerce actors and consumers. In this case, the government has an interest in preventing unfair business competition practices. The results of the analysis show that there have been a number of comprehensive legal protection instruments, including laws and regulations, and institutional structures to ensure law enforcement. However, there are weaknesses in aspects of regulation and institutional authority that require reform. Electronic commerce policy must be realized in accordance with national goals and interests, and oriented towards the protection of domestic business actors in Indonesia.